2021
DOI: 10.1111/jre.12914
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin: A review of experimental studies and mechanisms related to periodontitis treatment

Abstract: Curcumin is the main active ingredient of turmeric, which has a wide range of pharmacological effects, including antitumor, antibacterial, anti‐inflammatory, anti‐oxidation, immune regulation, and so on. Periodontitis is a prevalent oral inflammatory disease caused by a variety of factors. In recent years, many studies have shown that curcumin has a potential role on the treatment of periodontitis. Curcumin has been used in research related to the treatment of periodontitis in the form of solution, chip, gel, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 99 publications
(167 reference statements)
1
28
0
2
Order By: Relevance
“…The mechanism of periodontal disease involves the production of several inflammatory mediators. Periodontal pathogens activate NF-κB, Janus kinase (JAK)/signal transducer, activator of transcription (STAT), mitogen-activated protein kinases (MAPK), and other signaling pathways and produce inflammatory cytokines such as IL-6, TNF-α and IL-1β to promote inflammation ( Li et al, 2021 ). Curcumin, the active ingredient in turmeric, has various anti-inflammatory properties and may delay the disease process of periodontal disease in its initial stages.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of periodontal disease involves the production of several inflammatory mediators. Periodontal pathogens activate NF-κB, Janus kinase (JAK)/signal transducer, activator of transcription (STAT), mitogen-activated protein kinases (MAPK), and other signaling pathways and produce inflammatory cytokines such as IL-6, TNF-α and IL-1β to promote inflammation ( Li et al, 2021 ). Curcumin, the active ingredient in turmeric, has various anti-inflammatory properties and may delay the disease process of periodontal disease in its initial stages.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical trials, patients with periodontal diseases usually use curcumin as adjuvant therapy following subgingival instrumentation. Curcumin is commonly applied topically as a solution (mouthwash) or in solid form (curcumin sustained‐release tablet, gel, or chip) 306 …”
Section: Glucosamine and Chondroitin Sulfatementioning
confidence: 99%
“…Subsequent studies that tested use of curcumin as an adjunct to subgingival instrumentation have shown that its topical application significantly improved periodontal condition. Curcumin can directly and indirectly inhibit the activation of nuclear factor kappa‐light‐chain‐enhancer of activated B cells, Janus kinase/signal transducer and activator of transcription, and mitogen‐activated protein kinase signaling pathways, thus inhibiting the inflammatory cascade reaction involved in development of a variety of inflammatory diseases, as well as periodontitis 306 …”
Section: Glucosamine and Chondroitin Sulfatementioning
confidence: 99%
See 2 more Smart Citations